Gender Perception of Passengers in Aviation Services - Khurana, Poonam; Costin, Alina (International Journal of Psychosocial Rehabilitation, 2020)
India is moving through a growth phase in last 20 years. There are tremendous changes and aviation sector is not an exception to it. Situation of a woman is also changed due to women empowerment programmes. Woman is also decision makers of purchasing products and services so extantworkis and attempt to understand perception of gender in aviation services. Primary data is collected from passengers with structured questionnaire of five point likert scale and 212 responses were found suitable for further analyses due to completeness of every answer. Three variables tangibility, baggage facility and food were considered for the study. SPSS is used to compute desired results and checking the validation through t-test. Results of t-test suggest that substantial difference is not observed in the average agreement on cleanliness of washrooms in airplane between the males and females. Male respondents feel more cleanness of washroom during flight service than female respondents. Recommendations include there should be more check on inflight services specially enough options to choose for meals, compensation for lost or damaged, Cabin Appearance and less waiting time required for males and females as significant difference was found on these grounds.